2006
DOI: 10.1098/rspb.2006.3649
|View full text |Cite
|
Sign up to set email alerts
|

Locating the barnacle settlement pheromone: spatial and ontogenetic expression of the settlement-inducing protein complex ofBalanus amphitrite

Abstract: Barnacles are prominent members of hard substratum benthic communities and their study has been important to advances in experimental ecology and contemporary ecological theory. Having recently characterized the cue to gregarious settlement of Balanus amphitrite, the settlement-inducing protein complex (SIPC), we use two polyclonal antibodies to examine the tissue distribution and ontogenetic expression of this glycoprotein. These antibodies were raised against two separate peptides located near the N-and C-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 49 publications
3
56
0
1
Order By: Relevance
“…These results indicated that SIPC may be involved in adult-larva and larva-larva interactions during settlement. More detailed studies on the spatial and ontogenetic expression of SIPC have confirmed the previous findings and suggested that cyprids might detect this cue through contact with cuticle of adult barnacle (Dreanno et al, 2006a;Dreanno et al, 2006b;Dreanno et al, 2006c). Nevertheless, the SIPC receptor in cyprids is still unknown.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…These results indicated that SIPC may be involved in adult-larva and larva-larva interactions during settlement. More detailed studies on the spatial and ontogenetic expression of SIPC have confirmed the previous findings and suggested that cyprids might detect this cue through contact with cuticle of adult barnacle (Dreanno et al, 2006a;Dreanno et al, 2006b;Dreanno et al, 2006c). Nevertheless, the SIPC receptor in cyprids is still unknown.…”
Section: Introductionsupporting
confidence: 64%
“…SIPC is a cuticle glycoprotein involved in gregarious settlement behavior of B. amphitrite (Dreanno et al, 2006a;Dreanno et al, 2006b). On basis of its localization at cuticles, the authors suggested that besides functioning as a contact pheromone, SIPC may also act as a waterborne cue, possibly released through cuticle regeneration and bacterial degradation (Dreanno et al, 2006c).…”
Section: Discussionmentioning
confidence: 99%
“…The data show that the SIPC is expressed in all developmental stages investigated, confirming that this protein is not only produced by adults, but that it may also possess a function in larval-larval interactions (Dreanno et al 2006a). The SIPC is a large glycoprotein present in all organs that are lined by adult cuticular tissues, and evidence seems to indicate that the carbohydrate component of the SIPC plays a fundamental role in species recognition (Matsumura et al 1998a(Matsumura et al , 1998b.…”
Section: Resultsmentioning
confidence: 48%
“…The presence of hemocytes and proteins previously identified in hemolymph [i.e. SIPC (Dreanno et al, 2006)] in barnacle cement leads us to believe that barnacle hemolymph functions as a cement (Dickinson, 2008).…”
Section: Discussionmentioning
confidence: 99%